Ação da laserterapia de baixa intensidade (830nm) na regeneração muscular de ratos idosos - Rodrigues, Natalia Camargo (2009)
The elderly still go through physical changes, especially musculoskeletal disorders such as sarcopenia, changes in central and peripheral nervous system, blood hypoperfusion, regenerative changes contributing to atrophy and muscle weakness, undermining the activities of daily living (AVL). The regenerative process happens about the determination, proliferation and differentiation of satellite cells through activation of muscle-specific genetic program, which is regulated by specific transcription factors, known as myogenic regulatory factors (MRFs). But in the elderly because of changes in skeletal muscle-activation of MRFs are inefficient, hindering the process of regeneration. However, recent findings showed very promising results of low laser therapy (LLT) in muscle regeneration, but the effects of this therapy when associated with aging are still unknown. This project aims to evaluate the effects of (LLT), λ = 830nm, the tibial muscle of aged rats after cryolesioning. We used 56 male Wistar rats randomly divided into 4 groups (n = 7) of young rats from 3 months to 4 groups (n = 7) of aged rats, 10 months, divided into control groups (C), groups in which the right Tibialis anterior muscle (TA) was only irradiated (I), groups in which the AT was submitted to cryolesioning (CL) and groups where the TA muscle cryolesioning and was subjected to irradiation (LI). Treatment with the laser model of the DMC, Class 3B, energy of 0.87 J, was performed every 24 h for five consecutive days, with the first application 24 hours after induction of injury. On the sixth day after injury, with the animals anesthetized and the TA muscle was carefully dissected and removed, and then the animals were euthanaziated. We carried out histological analysis of the area of the lesion with toluidine blue, and counting of blood capillaries with hematoxylin-eosin. Through analysis by RT-PCR, it was possible to analyze the expression of MyoD and VEGF genes. The results showed that there was significant increase (p <0.05) of the expression of MyoD gene, VEGF gene and capillary blood count of more prominent in elderly victims and irradiated groups than in the young. Probably the LLT increased the maturation of satellite cells into myoblasts and miotubos, enhancing the regenerative process of aged rats irradiated.